An analysis of FDA-approved drugs for metabolic diseases. Issue 6 (June 2015) - Kinch, Michael S.; Umlauf, Sheila; Plummer, Mark
Highlights Growth in NMEs recently emphasizes genetic disorders. Genetic and nongenetic disorders utilize very different targets and approaches. Whereas pharma dominates diabetes, biotech is more prominent in genetic diseases.